Making food systems work for complementary feeding in low- and middle-income countries - Micronutrient Forum (Micronutrient Forum, 2024)
• Current food systems are failing young children worldwide. • Limited national supply, high levels of food loss and waste, high prices relative to household incomes, low appeal, and safety concerns are making nutritious complementary foods unavailable, inaccessible, unaffordable, and unappealing for those most in need. • Despite some successful efforts in adapting food systems to deliver safe and nutritious complementary foods, reaching low-income households with children aged 6-23 months remains a challenge. • A group of experts gathered in December 2023 to evaluate effective strategies and identify barriers to success in this area, and to define priority actions. • Food system actors and stakeholders need to collectively act on four core areas that hinder progress: filling the knowledge gaps, building local capacity, addressing implementation barriers related to business constraints and supply chain inefficiencies, and strengthening the enabling environment. • Thirteen recommendations were proposed across the four core areas, including six priority actions to urgently take forward.